Advances in transference-focused psychotherapy derived from the study of borderline personality disorder: clinical insights with a focus on mechanism. (June 2018) - Clarkin, John F; Cain, Nicole M; Lenzenweger, Mark F
Highlights: Randomized clinical trials demonstrate minimal differences between psychotherapies for borderline patients. Transference-focused psychotherapy (TFP) is effective in randomized trials but the mechanisms of change are not clear. Pre-treatment patient characteristics relate to improvement in TFP. Patients in TFP manifest brain changes following treatment consistent with enhanced emotional control. Abstract : The most current conceptualization of personality pathology emphasizes the assessment of the severity of selected domains of functioning involving lack of accurate perceptions of self and others that are common across the personality disorder categories. Advances in our understanding of personality pathology have stimulated further development of Transference-Focused Psychotherapy (TFP) for patients with borderline personality disorder, including treatment focus on both behavior and mental representations of self and others, the trajectory of change in TFP, and the extension of TFP principles to the entire domain of personality pathology.